Assessment of Saudi society’s attitudes towards implementing food polices of determining meal sizes and calories in food establishments - Zahra M Alhelal; Suzan H Tami (BMJ Nutrition, Prevention & Health)
AbstractIn 2020, the Saudi Food and Drug Authority introduced the Wajbati Rashaqati initiative to improve the quality of meals served in food establishments. The initiative included creating a menu for healthy meals with balanced nutritional elements; monitoring salt, sugar and fat content and reducing portion sizes. This study aimed to measure: (1) the awareness of Saudi adults regarding food calories and the method of calculating them; (2) the extent of Saudi adults’ knowledge of the initiative; (3) the readiness and extent of willingness of Saudi adults to commit to the initiative; (4) the relationship between Saudi adults’ body mass index (BMI), their calorie awareness and their readiness to implement the initiative and (5) the relationship between Saudi adults’ demographic factors, their calorie awareness and their readiness to implement the initiative. This cross-sectional study took place in the Eastern Region of Saudi Arabia, and the study data were collected through an electronic questionnaire. 519 Saudi adults participated in this study, and over 50% of the participants were female, married, with a bachelor’s degree and of a normal weight. Over 50% of the participants reported that they had knowledge of food calories and how to calculate their daily calories. Over 70% of the participants supported the initiative for determining the sizes and calories of foods available in food establishments, believing that this initiative might contribute to reducing obesity and chronic diseases. The χ2 analysis revealed a significant correlation between participants’ BMI and their commitment to daily calorie needs (p=0.001). Based on regression analysis findings, individuals highly aware of their daily calorie intake were more likely to practice portion control, understand the health implications of dietary choices, and support the Wajbati Rashaqati initiative. Sociodemographic characteristics influenced individuals’ knowledge and endorsement of the initiative. Females, low-income participants and those with a high school diploma or less were more supportive, knowledgeable and informed about the initiative. The results of this study may contribute as a guide to implementing the initiative. It also may help decision makers to raise community awareness regarding dietary reference values, as well as to plan programmes to improve dietary behaviours.